2022
DOI: 10.1093/hmg/ddac030
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide interaction analysis identified low-frequency variants with sex disparity in lung cancer risk

Abstract: Differences by sex in lung cancer incidence and mortality have been reported which cannot be fully explained by sex differences in smoking behavior, implying existence of genetic and molecular basis for sex disparity in lung cancer development. However, the information about sex dimorphism in lung cancer risk is quite limited despite the great success in lung cancer association studies. By adopting a stringent two-stage analysis strategy, we performed a genome-wide gene-sex interaction analysis using genotypes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Endogenous factors that potentially contribute to sex differences in age at diagnosis among lung cancer in patients who never smoke include the distribution of lung cancer histological subtypes, tumor mutations and genetic susceptibility [44,45,[56][57][58][59]. For example, females are at an increased risk compared to males of developing lung cancer with a driver mutation, such as the epidermal growth factor receptor (EGFR) [60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous factors that potentially contribute to sex differences in age at diagnosis among lung cancer in patients who never smoke include the distribution of lung cancer histological subtypes, tumor mutations and genetic susceptibility [44,45,[56][57][58][59]. For example, females are at an increased risk compared to males of developing lung cancer with a driver mutation, such as the epidermal growth factor receptor (EGFR) [60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…This study's observations cannot be further corroborated without accounting for other factors heavily intertwined with the sex, such as the familial history of T1D, the presence of high-risk SNPs (e.g., INS and PTPN22), and especially the viral background which we postulate to be the main environmental risk factor interacting with the CXADR. Recently, Li et al conducted a GWAS analysis of an European lung cancer cohort and found that a low-frequency CXADR SNP (rs208908) affected the risk for lung cancer in a sex-dependent manner (Li et al, 2022). Moreover, the authors suggested that the cause of this sex disparity stemmed from sex-based differential expression.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the CXADR is expressed by multiple cell types throughout the body, including respiratory epithelial cells, myocardial cells and pancreatic β-cells (Zanone et al, 2007;Excoffon, 2020;Owczarek et al, 2022). Lastly, in the context of disease pathology, enhanced expression of CXADRs has been observed in the pancreatic cells of individuals with T1D (Hodik et al, 2016), and a range of CXADR SNPs are associated with myocardial infarction (Marsman et al, 2011) and lung cancer (Li et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The main risk factor for developing NSCLC is smoking, which is preventable yet highly prevalent with over a billion smokers around the world [ 2 ]. Moreover, smoking and other environmental pollutants interact with biological factors such as aging and genetic risk variants to increase disease burden [ 3 , 4 , 5 , 6 ]. Furthermore, the NSCLC risk has been shown to correlate positively with the severity and duration of smoking and negatively with the time since smoking cessation [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%